Comparison of effects of static, proprioceptive neuromuscular facilitation and Mulligan stretching on hip flexion range of motion: a randomized controlled trial - Yıldırım, MS; Ozyurek, S; Tosun, OÇ; Uzer, S; Gelecek, N (Biology of Sport, 2016)
The aim of this study was to compare the effects of static stretching, proprioceptive neuromuscular facilitation (PNF) stretching and Mulligan technique on hip flexion range of motion (ROM) in subjects with bilateral hamstring tightness. A total of 40 students (mean age: 21.5±1.3 years, mean body height: 172.8±8.2 cm, mean body mass index: 21.9±3.0 kg • m-2) with bilateral hamstring tightness were enrolled in this randomized trial, of whom 26 completed the study. Subjects were divided into 4 groups performing (I) typical static stretching, (II) PNF stretching, (III) Mulligan traction straight leg raise (TSLR) technique, (IV) no intervention. Hip flexion ROM was measured using a digital goniometer with the passive straight leg raise test before and after 4 weeks by two physiotherapists blinded to the groups. 52 extremities of 26 subjects were analyzed. Hip flexion ROM increased in all three intervention groups (p<0.05) but not in the no-intervention group after 4 weeks. A statistically significant change in initial–final assessment differences of hip flexion ROM was found between groups (p<0.001) in favour of PNF stretching and Mulligan TSLR technique in comparison to typical static stretching (p=0.016 and p=0.02, respectively). No significant difference was found between Mulligan TSLR technique and PNF stretching (p=0.920). The initial–final assessment difference of hip flexion ROM was similar in typical static stretching and no intervention (p=0.491). A 4-week stretching intervention is beneficial for increasing hip flexion ROM in bilateral hamstring tightness. However, PNF stretching and Mulligan TSLR technique are superior to typical static stretching. These two interventions can be alternatively used for stretching in hamstring tightness.